2011
DOI: 10.1111/j.1526-100x.2011.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Structure in Austrocedrus chilensis Populations: Implications for Dryland Forest Restoration

Abstract: In South America, 94% of dry-temperate lands present some degree of environmental degradation, highlighting the need for ecological restoration. We analyzed geographic patterns of genetic variation in Austrocedrus chilensis, a dominant conifer of the steppe-forest ecotone in the eastern Andes, to examine its potential for restoration. We sampled 67 locations in Argentina and estimated genetic parameters to determine the effects of historical factors affecting diversity, together with inbreeding and gene flow, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 45 publications
0
29
0
1
Order By: Relevance
“…For example, the genetic structure of monospecific dryland forests of southern Argentina was assessed, focusing on the monotypic conifer Austrocedrus chilensis. While in the north marginal populations were relatively small and inbred yet genetically diverse, toward the south larger and relatively continuous populations had reduced diversity and showed signals of genetic admixture, highlighting the need for active restoration efforts (Souto et al 2011). This illustrates the risk of assuming that relatively small, isolated populations are genetically impoverished, and large continuous populations are highly genetically variable (Souto et al 2011).…”
Section: Applying the Principles Of Forest Landscape Restoration (Flr)mentioning
confidence: 99%
“…For example, the genetic structure of monospecific dryland forests of southern Argentina was assessed, focusing on the monotypic conifer Austrocedrus chilensis. While in the north marginal populations were relatively small and inbred yet genetically diverse, toward the south larger and relatively continuous populations had reduced diversity and showed signals of genetic admixture, highlighting the need for active restoration efforts (Souto et al 2011). This illustrates the risk of assuming that relatively small, isolated populations are genetically impoverished, and large continuous populations are highly genetically variable (Souto et al 2011).…”
Section: Applying the Principles Of Forest Landscape Restoration (Flr)mentioning
confidence: 99%
“…Souto et al () found higher levels of diversity and differentiation not only at species level but also at population level. As a general result, this could be attributed to sampling differences, because Souto et al () over‐represented the marginal forest patches from the steppe, which turned out to be the most diverse in both studies.…”
Section: Resultsmentioning
confidence: 97%
“…Souto et al () revealed eight enzymes, whereas Pastorino and Gallo () revealed just seven, of which five were coincident. One of the non‐coinciding enzymes in the set utilized by Souto et al () is cathodal peroxidase (Per Cat E.C.1.11.1.7).…”
Section: The Toolmentioning
confidence: 99%
See 2 more Smart Citations